(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
The National Prevention Plan (NPP) 2010-2012, approved by the Agreement between the Government, the Regions and Autonomous Provinces of Trento and Bolzano on 29 April 2010, called for Regions to adopt, by 31/12/2010, the Regional Prevention Plan (RPP) for implementing the interventions provided by the NPP 2010-2012. This article has considered and compared the different RPP’s. In an attempt to provide an outlook on the future medical prevention plans over the next few years in Italy, a comparison has been made between the RPP from 19 Regions and the Autonomous Province of Trento. This work has been focused on the actions identified in regional plans as a priority concerning the major common and innovative elements. The analysis of each RPP revealed a common plan to chronic degenerative diseases, because of the aging of the population in every Region of Italy. Other important common targets are: surveillance systems, vaccination programs and screening programs. Toscana and Liguria, more than other Regions, are engaged in the creation of networks involving various social actors. In some Regions there are projects aimed at eliminating social, economic or gender inequities, such as the project “women’s health” in the Region of Puglia. Toscana and Emilia-Romagna Plans pay attention to environment and pollution issues. Despite social, environmental and economic differences, the various Regions have common principles, concerning: life style, surveillance, vaccination and the screening for cancer.